Effectiveness of the reference service of the Claret School Library as percieved by its students - Bayhon, Allan C. (1996)
The study aims to; find out who uses the library's reference section more frequently among the high school students of Claret School; know if the students get the information they are looking for; know their reasons for using the library's reference section; find out the problems they encounter in the reference section and; to find out the needed improvements of its services based on the student's perceptions and suggestions. Out of the total population of 830, eight percent were picked out randomly to serve as respondents. The descriptive method of research was used and the questionnaire and interviews served as research instruments. The study revealed that most of the users were third year level students at 16 years of age. Majority of them preferred to use the encyclopedia; and the current awareness service or CAS was the most oftenly used information service. Their primary reason for using the library is to do their assignments. It was also found that the bottom line of all problems surfaced from the out-datedness of the books which made the service ineffective and deficient. Despite these problems, they claimed that the school was performing satisfactorily well.